Laboratory and Statistical Analysis of Children’s Infection with the Amoeba Parasite and its Impact on Immune Indicators in Salah Al-Din Governorate - Al-Tikrity, Dunia Abed Hussein (American Journal of Biology and Natural Sciences, 2025)
This study was conducted on children aged 1 to 6 years of age, both male and female, infected with the parasite Entamoeba histolytica. These children were admitted to Tikrit Teaching Hospital in Salah al-Din Governorate between June and December 2024. Stool samples were collected from children with acute diarrhea. One hundred samples were tested, and twenty tested positives using the direct swab method. The results showed an overall infection rate of 20%, with a higher rate among females (28%) compared to males (12%). The highest infection rate was recorded among children aged 5-6 years (25%), while the lowest was in the 1–2-year age group (10%). At the regional level, the highest infection rate among children with bloody diarrhea was in Baiji (36%), while the lowest was in Tikrit (8%). In terms of the monthly distribution of infection, July recorded the highest infection rate at 53.3%, while September recorded the lowest at 0%. The research investigated the effect of bloody diarrhea on certain immunological markers in the blood, such as Immunoglobulin A and Interferon gamma. A significant increase in Interferon gamma concentration was observed in children infected with E. histolytica, reaching 1512 compared to healthy children whose concentration was 834. IgA concentration also increased in infected children, reaching 5.83 compared to 3.68 in healthy children.